Genetic conditions of short stature: A review of three classic examples - Butler, Merlin G.; Miller, Bradley S.; Romano, Alicia; Ross, Judith; Abuzzahab, M. Jennifer; Backeljauw, Philippe; Bamba, Vaneeta; Bhangoo, Amrit; Mauras, Nelly; Geffner, Mitchell (Frontiers in Endocrinology, 2022)
Noonan, Turner, and Prader-Willi syndromes are classical genetic disorders that are marked by short stature. Each disorder has been recognized for several decades and is backed by extensive published literature describing its features, genetic origins, and optimal treatment strategies. These disorders are accompanied by a multitude of comorbidities, including cardiovascular issues, endocrinopathies, and infertility. Diagnostic delays, syndrome-associated comorbidities, and inefficient communication among the members of a patient’s health care team can affect a patient’s well-being from birth through adulthood. Insufficient information is available to help patients and their multidisciplinary team of providers transition from pediatric to adult health care systems. The aim of this review is to summarize the clinical features and genetics associated with each syndrome, describe best practices for diagnosis and treatment, and emphasize the importance of multidisciplinary teams and appropriate care plans for the pediatric to adult health care transition.